IPOs and SEOs in the US real estate industry - Radner, Philip (Springer Berlin Heidelberg, 2017)
Philip Radner analyzes equity financing phenomena and researches IPO underpricing and SEO announcement effects using data sets for US REITs. Moreover, he discusses underpricing theories and their applicability in the REIT context and gives a theoretical background on IPOs and on underpricing in particular. With this background at hand, the results out of this dissertation imply to focus on the wording in IPO documents as it can help to maximize IPO proceeds. In addition, he analyzes how to better time and announce subsequent equity financing events. It is expected that significantly underpriced issues attract more investors and that subsequent SEOs are then easier to conduct and typically raise more capital. Contents IPO Underpricing in the Real Estate Industry: Analytical Review of the Literature Textual Analysis of REIT IPO Prospectuses: Quantifying Company Rhetoric as an Indicator of Underpricing An Analysis of Announcement Effects of Seasoned Equity Offerings by REITs since 2008 Target Groups Scientists and students in the field of real estate, real estate capital markets, real estate finance and finance About the Author Philip Radner wrote his dissertation at the Real Estate Management Institute (REMI) of the EBS Business School. He currently works in Real Estate M & A Advisory.
Keywords: Real estate business.; elektronické knihy; electronic books